AN OPD BASED PROSPECTIVE EXPLORATORY STUDY OF DERMATOPHYTOSIS - FOCUS ON TREATMENT OUTCOMES, MEDICATION ADHERENCE, AND QUALITY OF LIFE - MUKHERJEE, SOUGATA; BAGCHI, CHIRANJIB; CHATTERJEE, KINGSHUK; DAS, AVIK; KUMAR TRIPATHI, SANTANU (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The study was planned primarily to judge the effectiveness, safety, and adherence of the prescribed treatments in dermatophytosis along with the effect on the Quality of Life (QoL) of the affected individuals. Methods: In this prospective observational study, spanning over 5 months, participants (dermatophytosis patients) were assessed at baseline and 6 week-follow-up at study site. Information about their clinical presentation, QoL (Quality of Life) parameters, medication adherence, and adverse drug reaction (ADR) were entered in the Case Report Form (CRF) prepared by utilizing global standard tools such as 5D-itch scale, Dermatology Life Quality Index (DLQI), Medication Adherence Rating Scale (MARS), and WHO-ADR reporting form respectively. Results: Total 60 subjects (33 males and 27 females) had completed the study. Overall, tinea cruris (40%) was the most common variety followed by combination of tinea corporis and cruris (35%), tinea corporis (20%), and tinea incognito (3%). Pruritus was the predominant symptom. There was a significant (p<0.001) improvement of both 5D-itch & DLQI scores from baseline to follow-up stage (after 6 weeks). Treatment regimens were well tolerated (only eight subjects reported any adverse event such as gastric irritation and sedation). Medication adherence to the prescribed treatment was good; (mean MARS score 7.588±1.82). Mostly prescribed regimen was a combination of antifungal (oral plus topical) and antihistamine tablet (58/60, 96.66%). The most common drug combination was capsule itraconazole, luliconazole cream, and cetirizine or levocetirizine tablet with or without ketoconazole soap (35/60, 58.33%). Conclusion: Prescribed treatment regimen for dermatophytosis was effective, tolerable, acceptable with high medication adherence and also improved the QoL of the study subjects.